(untitled) (Indonesian Journal of Science and Technology, 2025)
Water scarcity in extreme climates presents a global challenge directly linked to Sustainable Development Goals (SDGs), particularly SDG 6 (Clean Water and Sanitation). This study introduces an innovative solar still design using nanofluid encapsulation to enhance freshwater production because conventional systems often struggle with limited efficiency. The modified solar still employed sealed glass tubes containing CuO nanofluid, improving solar energy absorption and heat retention because the nanofluid could enhance thermal conductivity. The system maintained higher operational temperatures, leading to increased evaporation and freshwater yield. The encapsulation prevented nanoparticle contamination, ensuring water safety and long-term system stability. This approach demonstrates significant potential to support sustainable freshwater solutions aligned with global SDG targets under harsh environmental conditions.